Aberrant DNA methylation associated with the development of metabolic dysfunction-associated fatty liver disease - O.E. Abaturov; A.O. Nikulina; O.O. Rusakova (Zaslavsky O.Yu., 2024)
The literature review deals with DNA methylation, a key epigenetic mechanism that controls the activity of gene transcription, plays a decisive role in the formation of genomic imprinting, gene silencing, X-chromosome inactivation, RNA splicing, DNA repair, cell differentiation and cell reprogramming, and also determines the occurrence and development of liver steatotic lesions and metabolic disorders. Methylation of DNA cytosine dinucleotide (CpG) can be represented in two types: de novo CpG methylation, which is carried out by 5mC DNA writers - DNA-(cytosine-5)-methyltransferase (DNMT) 3a and 3b, and supporting DNA methylation, which is performed by DNMT1 during DNA replication. It has been found that the maintenance DNA methylation allows the preservation of the methylation pattern characteristic of progenitor cells in the cells of the new generation, and the DNA methylation of the gene body is associated with its increased expression. Active demethylation of 5mC is carried out by TET dioxygenases, including three enzymatic representatives: TET1, TET2 and TET3. It has been demonstrated that aberrant methylation of DNA nucleotides is directly related to the activity of lipid synthesis, the degree of oxidative stress, the development of liver steatosis, low-grade inflammation, insulin resistance, and the progression of liver fibrosis. The authors presented in detail the functions and features of DNA methyltransferases, erasers, and readers of 5mC sites; possible violations of the balance of activity of writers and erasers of 5mC DNA; DNA methylation landscape and patterns; clinical significance of DNA methylation signatures in metabolic dysfunction-associated fatty liver disease. Global hypomethylation of genome, at least 55 genes, is observed in patients with metabolic dysfunction-associated fatty liver disease. The authors emphasize that the use of DNA methylation signatures is a promising direction for early diagnosis and prognosis of the course of metabolic dysfunction-associated fatty liver disease, while the study of molecular components of DNA methylation mechanisms involved in the regulation of gene expression, the dependence of their activity on exposure to the exposome will allow to personalize and improve recommendations for lifestyle and diet modification in patients with metabolic dysfunction-associated fatty liver disease.